PECULIARITIES OF DISOVERY OF HIDDEN OBJECTS OF ARTIFICIAL ORIGIN IN CUSTOMS CONTROL - Tarasenko, Y. S.; Smirnov, V. V.; Prokopovich-Tkachenko, D. I. (Systems and Technologies, 2019)
With the advent of near and later non-linear types of radar, it be came pos-sible to solve, in addition to radar, a number of other applied problems, such as problems of diagnostic and flaw detection, customs control, humanitarian demining, forensic science, archeology and construction with terrorism. The article deals with the actual problem of peculiarities of detection of hidden objects of artificial origin, which are in the conditions of interaction with the control and measuring radio equipment of customs control, which do not sa- tisfy the criterion of the far zone. The object/targets catering characteristics were compared both in the form of a complex reflection coefficient (obtained using a radio channel model) and in the form of an effective object/targets catering plane. In general, the object/target is displayed from the point of view of aniso-tropic fixed-point emitter f for a fixed stationary orientation of the signal/signal relative to the propagation direction of the incident and reflected waves of stabi- lity of the polarization characteristics of the transmitting and receiving antennas of the radar. The basic nonlinear radar equation is described, which describes the be-havior of a two-component radio system, in which some amplitude-frequency transformations of the radar transmitter sounding transducer signal are intro-duced into the reflection by nonlinear elements of the irradiated object/target. Basically, nonlinear radio signals describing the behavior of a two-component radio system are considered, since the secondary reflection contains nonlinear signal elements that are often used to transmit frequency signals. The results of the nonlinear transformation of the sounding signal on non-linear elements with harmonic frequencies are combinations there of are based on the analysis of the scattering properties of the model in the form of antennas with the nonlinearities included there in. The task of expediency of carrying out full-scale experimental researches of character of behavior of effective reflection ability of specific typical objects for drawing up of a databank containing portraits of hidden images of typical cus-toms control object isset.